2018
DOI: 10.1016/j.ecoleng.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Typha latifolia paludiculture effectively improves water quality and reduces greenhouse gas emissions in rewetted peatlands

Abstract: Typha latifolia paludiculture effectively improves water quality and reduces greenhouse gas emissions in rewetted peatlands

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 66 publications
3
36
0
Order By: Relevance
“…Lishawa et al (2019) suggested that restoration techniques of cattail dominant areas should focus on periodic treatments including biomass removal, in order to preserve the native biodiversity. Vroom et al (2018) proposed that T. latifolia can be utilized for the restoration of peatlands after their rewetting, because of the species capacity to control nitrogen and phosphorus concentrations from surface and pore water, as well as regulate CH 4 and N 2 O emissions. Nevertheless, the selection of cattail species for potential phytoremediation must be based upon the species invasiveness risk (Bonanno and Cirelli, 2017;Gikas et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Lishawa et al (2019) suggested that restoration techniques of cattail dominant areas should focus on periodic treatments including biomass removal, in order to preserve the native biodiversity. Vroom et al (2018) proposed that T. latifolia can be utilized for the restoration of peatlands after their rewetting, because of the species capacity to control nitrogen and phosphorus concentrations from surface and pore water, as well as regulate CH 4 and N 2 O emissions. Nevertheless, the selection of cattail species for potential phytoremediation must be based upon the species invasiveness risk (Bonanno and Cirelli, 2017;Gikas et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The following is available online at http://www.mdpi.com/2073-4441/12/3/629/s1, Supplementary S1: Processes Driving Water Purification, Characteristics of Designated Types of Wetland Buffer Zones (WBZs), and the Scope of Work Needed to Create Each WBZ Type. References [23,[70][71][72][73][74][75][76][77][78][79][80][81] are cited in the supplementary materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…The fate of organic carbon and nitrogen is also influenced by microbial communities associated with methane cycling and nitrogen cycling in which CH 4 and N 2 O are produced [13, 14]. While decent efforts were invested to investigate the influence of rewetting on the emissions of greenhouse gases (GHGs) [15-18], extracellular enzyme activities [19], dissolve organic carbon [20, 21], and water chemistry [15, 19], little is known about the changes of microbial communities driving these processes.…”
Section: Introductionmentioning
confidence: 99%